Análisis térmico en compuestos de HDPE reforzados con fibras de pinus radiata (2017)
"Wood Composite Materials (WPC) are composites that consist of a polymeric matrix reinforced with wood fibers... In this research, the effect of the components over the thermal diffusivity was analyzed using different commercial formulations. DSC and thermal diffusivity analysis where performed over the samples, with a FTIR analysis to identify the chemical composition of each one. The effect of the wood on the thermal properties was also analyzed." -- Tomado del Formato de Documento de Grado.